Honour and Fighting Social Advancement in the Early Modern Age - Gassmann Jürg (Acta Periodica Duellatorum, 2015)
The article considers the importance of military service in social advancement, here understood as filling the role of “prince” in feudal law and thus participating in the government of an estate, in the transition from the Late Middle Ages to the Renaissance or Early Modern Age. In the context of a city burgher or a petty noble or knight advancing into a government role, did honour require that the individual have experience in fighting – in war, military organisation and leadership? How did mercenaries figure? What role, if any, did Fechtmeister, Fechtbücher, Fechtschulen or Kriegsbücher play?